2023
DOI: 10.1039/d2dt04039e
|View full text |Cite
|
Sign up to set email alerts
|

The acid-mediated isomerization of iridium(iii) complexes with cyclometalated NHC ligands: kinetic vs. thermodynamic control

Abstract: The fac isomers of iridium(iii) complexes with metalated N-heterocyclic carbene (NHC) ligands are transformed cleanly into the mer isomers when solutions of the complexes are treated with first HNTf2 and then NEt3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(95 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, the reversible C–H activation and cyclometalation of aryl appendages is also responsible for the selective formation of a single product in the presence of sodium acetate at elevated temperature. 45,46…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the reversible C–H activation and cyclometalation of aryl appendages is also responsible for the selective formation of a single product in the presence of sodium acetate at elevated temperature. 45,46…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the reversible C-H activation and cyclometalation of aryl appendages is also responsible for the selective formation of a single product in the presence of sodium acetate at elevated temperature. 45,46 A single crystal X-ray diffraction study on m-Ir(dfp) 3 and f-Ir (tBpp) 3 was executed to confirm the coordination arrangement of chelates. Particularly, the unique Ir-C1 vector, that is uniquely located trans to the Ir-C (carbene) vector, is the shortest among all Ir-C (aryl) vectors, showing the reduced trans-effect of carbene in reference to the aryl entities.…”
Section: Preparation and Characterizationmentioning
confidence: 99%
“…Moreover, no m ‐isomer was detected within this system, despite that acid treatment was known to give the reversed fac ‐to‐ mer transformation under controlled condition. [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, no m-isomer was detected within this system, despite that acid treatment was known to give the reversed fac-to-mer transformation under controlled condition. [21] All Ir(III) complexes showed an essentially identical M + ion in their mass spectra. The 1 H and 19 F NMR analyses suggested that f-ct6a possesses the highly symmetrical arrangement of chelates, i.e., possible existence of C3 symmetry.…”
Section: Syntheses Of the Pro-chelate And Ir(iii) Complexesmentioning
confidence: 97%
“…29 A recent report on homoleptic Ir( iii ) complexes bearing metalated N-heterocyclic carbenes may also provide clues to the possible intermediates and pathway of isomerization processes. 30…”
Section: Resultsmentioning
confidence: 99%